Evaluation of the Reddesa Chart, a New Red Desaturation Testing Method, for Optic Neuritis Screening and Grading in Clinical Routine - Bruegger, Dominik; Koth, Anna-Lucia; Dysli, Muriel; Goldblum, David; Abegg, Mathias; Tschopp, Markus; Tappeiner, Christoph (Frontiers in Neurology, 2022)
Background. Optic neuritis usually leads to reduced color-sensitivity. Most often the change of red color, so called red desaturation, is tested in clinical routine. The aim of this study was to test the feasibility of the Reddesa chart, a new red desaturation test based on polarization, as a screening method for optic neuropathy. Methods: A total of 20 patients with unilateral optic neuritis and 20 healthy controls were included in this prospective pilot study. Ophthalmological examination included assessment of best corrected visual acuity (BCVA), slit lamp examination, fundoscopy, testing of relative afferent pupillary defect (RAPD) and red desaturation with the red cup test and the Reddesa chart. Results: The mean BCVA in the optic neuritis group was 0.76±0.36 in the affected eye (95% of eyes with RAPD, 75% of eyes with difference in the Reddesa test) and 1.28±0.24 in the healthy eye, whereas in the control group BCVA was 1.14±0.11 in the right eye and 1.15±0.14 in the left eye (none of the eyes with RAPD or abnormal Reddesa test). In our study, the Reddesa test showed a positive predictive value of 100% and a negative predictive value of 80% for detecting optic neuritis. Conclusion: The Reddesa chart allows to quantify red desaturation and has the potential to be implemented as a screening test in clinical routine.